Teologi Sistematika dan Pendidikan Kristen di Gereja - Rotua, Dewi Magdalena; Birahim, Susanti; Nizar, Happy Wahyu (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2025)
Systematic theology plays a vital role in shaping Christian education within the church's life. This article explores the connection between theological doctrines and educational practices by emphasizing the significance of biblical principles, doctrinal accuracy, and theological reflection in enhancing Christian teaching. The study adopts a qualitative-descriptive approach, employing a literature review method to analyze and synthesize theological and educational sources, including Scripture, academic books, and peer-reviewed journals. Its goal is to examine the biblical foundations and practical strategies for implementing contextual and effective Christian education. The findings highlight that integrating systematic theology into church education is essential for cultivating spiritually mature believers with a thorough understanding of faith and preparing them for meaningful ministry. Additionally, this article offers a fresh perspective by linking theology and education while discussing practical strategies for application across various church ministries